Pengaruh Pemilihan Kepala Daerah terhadap Employment Transition: Analisis Sektor Formal dan Informal pada Tingkat Individu di Pulau Jawa - Beni Teguh Gunawan (Jurnal Kependudukan Indonesia, 2018)
Local elections (pilkada) have become a political phenomenon which presumably may impact other sectors, including the employment and labour sector. This sector is one of the attractive commodities to be sold by the head of government, thus vulnerable to the interests of certain parties. Economic rationale is all too often used by the electoral candidate through promises to provide employment, and making it easier to attract sympathy from the unemployed. This paper presents the results of the study about the impact of the election on the employment transition. The analysed impact is the change in the employment sector one year before the election (t-1) until the year in which election was hold (t). This study analyzes the 2010 population census data with a multinomial logit (MNL) analysis approach. Empirical results show that district elections have a positive and significant effect on the transition from unemployment to working in the informal and formal sectors. While individuals who have previously worked in the formal sector tend to survive in the sector. On the other hand, it turns out that the district elections did not have a significant impact on individuals who previously worked in the informal sector